Controlled Lithium Deposition - Zhang, Simeng; Yang, Gaojing; Li, Xiaoyun; Li, Yejing; Wang, Zhaoxiang; Chen, Liquan (Frontiers in Energy Research, 2022)
Lithium metal is a promising anode material for its low redox potential and high theoretical specific capacity. However, the commercial application of the lithium metal anode is hindered with safety concerns arising from the uncontrolled growth of the lithium dendrites and significant volume variation during the lithium plating and stripping processes. Modification to the current collector is effective in tailoring the morphology of the deposited lithium and improving the cycling performance of the lithium metal batteries This review summarizes at first the global research advances in the structural design and the selection of the current collectors and their textures. It then presents some of our efforts in realizing controlled lithium deposition by designing current collectors in three aspects, lithium deposition induced by the micro-to-nano structures, lithiophilic alloys and iron carbides. Finally, conclusions and prospects are made for the further research of the current collectors.